A-17 Effects Of Parental Mental Health On Patient and Parent-Reported Anxiety Symptoms Following Concussion In Adolescents. (13th July 2022) - Gomes, D; Manderino, L M; Preszler, J; Collins, M W; Pan, R; Santos, J; Versace, A; Kontos, A P
Abstract: Purpose: Examine the impact of parental mental health history on patient and patent-reported post-concussion symptoms of anxiety. Methods: Participants included 105 adolescents (42.9% male), 12–18 years old, including concussion patients (n = 72, 3.42 ± 1.7 days post-injury) and age-and-sex matched controls (n = 33). Patients and parents completed the Screen for Child Anxiety Disorders, Parent and Child versions (SCARED-P, SCARED-C) and medical histories. T-tests were used to compare control/concussed responses on the SCARED. Logistic regression (LR) was used to evaluate group predictors, as well as high/low (i.e., >21 PCSS total score) concussion symptom groups at 30 days post-injury. Results: Results indicated that concussed SCARED-C (controls: M = 7.88 SD = 7.55, concussed: M = 13.4 SD = 11.42), (t[103] = −2.53, p = 0.01) and SCARED-P (controls: M = 3.55 SD = 3.62, concussed: M = 6.72 SD = 7.12), (t[103] = −2.42, p < 0.01) scores were higher than controls. SCARED-C/SCARED-P scores were not predictive of high/low symptom report at 30 days post-injury, X 2 (2, n = 59) = 3.46, p = 0.18. The stepwise LR model was significant, X 2 (1, n = 105) = 7.34, p = 0.007; SCARED-C scores were predictive of concussion group inclusion, SCARED-P scores were not. In analyses of only patients whose parent reported a mental health history (22/105, 21%), there was no significant difference between control and patients on the SCARED-C, t(20) = −1.82, p = 0.08, or SCARED-P, t(20) = −0.34, p = 0.74. SCARED-C/SCARED-P scores did not predict control/concussion group inclusion, X 2 (2, n = 22) = 5.04, p = 0.08. Conclusions: SCARED-P/SCARED-C scores effectively differentiated between groups: patients and parents reported higher anxiety symptoms. The inclusion of parents with mental health diagnoses precluded the SCARED from differentiating controls from patients.